Nonaqueous capillary electrophoresis and quantum chemical calculations applied to investigation of acid–base and electromigration properties of azahelicenes. Issue 5 (30th December 2021) - Šolínová, Veronika; Štěpánová, Sille; Jančařík, Andrej; Klívar, Jiří; Šámal, Michal; Stará, Irena G.; Chocholoušová, Jana Vacek; Vacek, Jaroslav; Starý, Ivo; Kašička, Václav
Abstract: Nonaqueous capillary electrophoresis (NACE) using methanol (MeOH) as a solvent of the BGEs and quantum mechanical density functional theory (DFT) have been applied to determine the thermodynamic acidity (ionization) constants (p K a ) of mono‐ and diaza[5]helicenes, mono‐ and diaza[6]helicenes, and their dibenzo derivatives in MeOH and water. First, the mixed acidity constants, p K a, MeOH mix pK_a, MeOH^mix, of ionogenic pyridinium groups of azahelicenes and their derivatives in MeOH were obtained by nonlinear regression analysis of pH dependence of their effective electrophoretic mobilities. The effective mobilities were measured by NACE in a large series of methanolic BGEs within a wide conventional pH range (pHMeOH 1.6–12.0) and at ambient temperature (21–26°C) in a home‐made CE device. Prior to mixed acidity constant calculation, the effective mobilities were corrected to reference temperature (25°C) and constant ionic strength (25 mM). Then, the mixed acidity constants were recalculated to the thermodynamic acidity constants p K a, MeOH by the Debye–Hückel theory of nonideality of electrolyte solutions. Finally, from the methanolic thermodynamic p K a, MeOH values, the aqueous thermodynamic p K a, H 2 O pK_a, H_2O constants were estimated using the empirical relations between methanolic and aqueous acidity constants derived for structurally related pyridine derivatives. Depending on the number and position of the nitrogen atoms in their molecules, the analyzed azahelicenes were found to be weak to moderate bases with methanolic p K a, MeOH in the range 2.01–8.75 and with aqueous p K a, H 2 O pK_a, H_2O in the range 1.67–8.28. The thermodynamic p K a, MeOH obtained by the DFT calculations were in a good agreement with those determined experimentally by NACE.